Evaluation of ankle ligaments with CT: A feasibility study. Issue 134 (January 2021) - Sterzik, A.; Mueck, F.; Wirth, S.; Baumbach, S.F.; Polzer, H.; Reiser, M.; Maxien, D.
Abstract: Purpose: This study aims to systematically investigate if normal ankle ligaments can be assessed with CT imaging, using MRI as reference standard. Methods: 35 patients (mean age: 47 ± 15 years; female n = 19) with combined CT and MRI exams and without MR-morphologic signs of ankle ligamental injury were retrospectively identified. 3 readers independently evaluated the syndesmotic, the lateral and medial ankle ligaments in terms of visibility on a 4-point Likert scale (0–3 points) in multiplanar MDCT images in standard bone kernel reconstructions. In consensus CT-based ligament density and thickness were measured and the appearance was rated for each ligament. Results were compared and validated with corresponding MRI images. Results: Almost all ankle ligaments identified in MRI images could be adequately depicted in standard multiplanar bone kernel CT images with a mean visual score of 2.7/3 (± 0.2). Difficulties in CT morphological delineation of ankle ligaments occurred in cases of filiform TNL and TCL and in cases of concurrent soft tissue edema. Interreader agreement for the CT-assessment of ankle ligaments was excellent, with Fleiss Kappa values >0.8. Mean density of evaluated medial and lateral ankle ligaments was 68 ± 2.9 HU, with substantially inter- and intraindividual variations. Thickness measurements and assessment of appearance of ankle ligaments showed a good concordance between CT and MRI. Conclusions: Assessment of normal ankle ligaments via standard CT in bone kernel reconstructions is feasible, with some restrictions concerning the medial collateral ligaments and in the presence of soft tissue edema.